A critical review on the development and challenges of concentrated solar power technologies. (October 2021) - Shahabuddin, M.; Alim, M.A.; Alam, Tanvir; Mofijur, M.; Ahmed, S.F.; Perkins, Greg
Abstract: Solar energy is considered to be one of the most promising renewable and sustainable energy sources. Two key technologies such as photovoltaic and concentrated solar power are mainly used to convert solar radiation, out of which photovoltaic directly converts solar radiation into electricity, while concentrated solar power technology converts solar radiation both into heat and electricity. The key advantages of concentrated solar power technology over photovoltaic is its capability of storing heat energy which can be utilised in the absence of sunlight, overcoming the limitation of the intermittent nature of solar power. Currently, the cost for the concentrated solar power with storage is about 9.0 ¢/kWh (same as commercial photovoltaic system), which is expected to drop at ~5.0 ¢/kWh by 2030. Besides four mainstream concentrated solar power technologies, this paper reviewed the application of concentrated solar power in thermolysis, thermochemical cycle, hydrocarbon cracking, reforming and solar gasification. Based on the literature review, this study has outlined the key challenges and prospects of concentrated solar power technologies. The main challenge in thermolysis is the requirement of very high temperature, while the thermochemical cycle is inefficient. Solar thermal cracking, reforming, and gasification integrate carbonaceous fuel to produce synthesis gas and hydrogen and therefore are not emission-free. The concentrated solar power technologies require further development and cost reductions before they can be scaled up to have a meaningful impact on renewable energy targets towards 2050.